The American Red Cross : out of catastrophe come charity and controversy (A) - Hulett, Joanne M.; Malaier, Angela Bree; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Following the 9/11 terrorist attacks, the American Red Cross collects so many donations for victims that it creates a special fund called the Liberty Fund to handle more than $564 million. When the public discovers significant portions of the fund will not be used for the families of those who died in the bombing, Congress intervenes and begins investigating Red Cross activities. The charity is also under fire for not cooperating with other charities in the distribution of monies or using proper screening to determine genuine requests for relief. In the midst of the largest scandal ever for the Red Cross, its CEO and president Dr. Bernadine Healy resigns and the Board of the Red Cross, specifically Chairman David McLaughlin, must find a way to rebuild trust in the Red Cross and ensure the public that the funds collected are distributed properly.
Originally published: Hulett, J. M., Malaier, A. B., & ORourke, J. S. (2002). The American Red Cross: Out of catastrophe come charity and controversy (A). 02-08 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; American National Red Cross -- Case studies; September 11 Terrorist Attacks, 2001 -- Case studies; United States -- Social conditions -- 21st century -- Case studies